Current Perspectives on the Immunosuppressive Niche and Role of Fibrosis in Hepatocellular Carcinoma and the Development of Antitumor Immunity. (January 2022) - Aoki, Tomoko; Nishida, Naoshi; Kudo, Masatoshi
Immune checkpoint inhibitors have become the mainstay of treatment for hepatocellular carcinoma (HCC). However, they are ineffective in some cases. Previous studies have reported that genetic alterations in oncogenic pathways such as Wnt/β-catenin are the important triggers in HCC for primary refractoriness. T-cell exhaustion has been reported in various tumors and is likely to play a prominent role in the emergence of HCC due to chronic inflammation and cirrhosis-associated immune dysfunction. Immunosuppressive cells including regulatory T-cells and tumor-associated macrophages infiltrating the tumor are associated with hyperprogressive disease in the early stages of immune checkpoint inhibitor treatment. In addition, stellate cells and tumor-associated fibroblasts create an abundant desmoplastic environment by producing extracellular matrix. This strongly contributes to epithelial to mesenchymal transition via signaling activities including transforming growth factor beta, Wnt/β-catenin, and Hippo pathway. The abundant desmoplastic environment has been demonstrated in pancreatic ductal adenocarcinoma and cholangiocarcinoma to suppress cytotoxic T-cell infiltration, PD-L1 expression, and neoantigen expression, resulting in a highly immunosuppressive niche. It is possible that a similar immunosuppressive environment is created in HCC with advanced fibrosis in the background liver. Although sufficient understanding is required for the establishment of immune therapies of HCC, further investigations are still required in this field: